Awareness and Uptake of Antenatal Care Service Among Women in Iddo Local Government Area of Oyo State, Nigeria - Fadairo, O. S.; Idiale, M. (The Nigerian Journal of Rural Extension and Development, 2023)
Various health challenges of neonatal death, still birth and maternal mortality are traceable to ineffective antenatal care programmes among others. The study therefore investigated awareness and uptake of antenatal care service content among women in Iddo local government area of Oyo State. Using snow ball research technique, 90 breast feeding mothers were selected from the study area and data was collected using structured questionnaire on their personal characteristics, awareness and uptake of Antenatal Care (ANC) service content, ANC service providers in the study area and constraints faced by mothers in accessing ANC services. Mean age of respondents was 36.3 and 78.8% had below secondary school education. Most of mothers were aware of each of the content of antenatal care services with highest awareness observed for urine test (83.3%) followed by blood test (82.2%). Uptake of ANC components was highest for tetanus toxoid (x?=2.2) followed by anti-malarial (x?=2.0) and blood test (x?=1.7). Religious centers (x?=2.31) received the highest patronage from mothers who attended antenatal care. Delay respondents faced at health centers before they received attention from service providers ranked as the highest constraint they faced in up-taking ANC services (x?=2.32). Significant relationship existed between respondents location (?2=15.89; p<0.05) and uptake of ANC. Efforts aimed at decreasing the existing wide gap between health workers and clientele ratio and to increase the number of health facilities providing antenatal services should be given urgent attention.